2019
DOI: 10.1002/gps.5222
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of glial cell line‐derived neurotrophic factor and multiple neurotransmitters: In relation to cognitive performance in Parkinson's disease with mild cognitive impairment

Abstract: ObjectivesMild cognitive impairment is a common non‐motor feature of Parkinson's disease, termed PD‐MCI. But there is a scarcity of data on the role of glial cell line‐derived neurotrophic factor (GDNF) and neurotransmitters in pathogenesis of PD‐MCI. The aim of this project was to detect the serum levels of GDNF and multiple neurotranmitters and explore their relationships with cognitive performance in PD‐MCI patients.MethodsNeuropsychological testing was administered to PD patients and healthy controls to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Beyond its involvement in PD pathology, a recent study reported a correlation between serum levels of GDNF and other neurotransmitters with the degree of cognitive impairment in PD patients. 40 These findings suggest that DNA methylation may be upstream of transcriptional deregulation of genes associated with cognitive decline and neuropathology, thus supporting the specificity of the signal we captured.…”
Section: Discussionsupporting
confidence: 68%
“…Beyond its involvement in PD pathology, a recent study reported a correlation between serum levels of GDNF and other neurotransmitters with the degree of cognitive impairment in PD patients. 40 These findings suggest that DNA methylation may be upstream of transcriptional deregulation of genes associated with cognitive decline and neuropathology, thus supporting the specificity of the signal we captured.…”
Section: Discussionsupporting
confidence: 68%
“…Glucosylceramidase (GBA), leucine-rich repeat serine/threonine-protein kinase 2 (LRRK2), and α-Syn mutations have been associated with PD-MCI and PDD ( Aarsland et al, 2017 ). Recent studies have shown that high levels of serum/plasma α-Syn and low levels of serum glial cell line-derived neurotrophic factor (GDNF), miRNA-29s (miR-29s), vitamin D, and 25-hydroxyvitamin D may be involved in the cognitive impairment of PD-MCI and PDD patients ( Bougea et al, 2020 ; Han L. et al, 2020 ; Liu Y. et al, 2020 ; Santangelo et al, 2020 ). Importantly, low levels of epidermal growth factor (EGF) may be predictive of cognitive decline ( Pellecchia et al, 2013 ).…”
Section: Clinical Features Of Parkinson’s Disease Mild Cognitive Impairment and Parkinson’s Disease’s Disease Dementiamentioning
confidence: 99%
“…For example, in ageing mice brain tissue, increased dopamine levels were observed after supplementation with Aronia melanocarpa [19]. Interestingly, serum levels of dopamine metabolites were recently found to be negatively associated with cognitive impairment in Parkinson's disease patients [49]. Furthermore, supplementation with berry anthocyanins in rats resulted in increased hippocampal insulin-like growth factor (IGF)-1 expression [50].…”
Section: Discussionmentioning
confidence: 99%